Healthy Lifestyle Programs in Out-of-Home Care: Implementing Preventative Trauma-informed Approaches at Scale. Issue 1 (2nd January 2022) - Pizzirani, Bengianni; Green (nee Cox), Rachael; O'Donnell, Renee; Skouteris, Helen
ABSTRACT: From 2012 to 2014, we developed and subsequently evaluated the Healthy Eating, Active Living (HEAL) intervention—an obesity prevention and healthy lifestyle program designed for young people living in residential out-of-home care (OoHC). Based on quantitative (i.e., a randomised trial) and qualitative (i.e., semi-structured interviews) data and an iterative process of redevelopment, the program has evolved from taking a behavioural obesity prevention approach to now being underpinned by a trauma-informed care approach at a systems level. In this paper we outline the theoretical and empirical foundations of the HEALing Matters intervention that is currently being implemented at scale. In addition, we outline how our knowledge translation framework informed the iterative improvement of our intervention with a focus on stakeholder and end-user engagement, partnership, and codesign along the way. IMPLICATIONS There is a strong need for trauma-responsive health-focused programs and interventions within OoHC contexts. HEALing Matters addresses the need for trauma-informed approaches that encourage health behaviour change in young people living in OoHC. Policy, standards, and recommendations must not only acknowledge, but prioritise, the impact of trauma on health-related lifestyle behaviours in order to identify strategies to help address this impact.